ANALISIS ALAT PENILAIAN KOMPETENSI BATIK BERBASIS AUTHENTIC ASSESSMENT DI SMK NEGERI 14 BANDUNG - Faridah, Nida; Abas, Tati; Widiaty, Isma (Prodi PKK - Departemen PKK - Universitas Pendidikan Indonesia, 2017)
The problem in this research is the lack of development of assessment tools, especially in the aspect of the assessment is used as a reference in the assessment of the competence of batik. This study aims to: (1) analyzing tool competency assessment batik used in schools include the completeness of the components of assessment tools, assessment tools preparation stage batik, tool assessment phase of the work process of batik, tool assessment phase of the product of batik (2) develop assessment tools instructional practices authentic batik competency-based assessment. This research uses descriptive method. Population and sample in this study to be an object that is an assessment tool batik competency practices shaped sections. The technique of collecting data using interviews, documentary studies, and activities of expert judgment. The analysis showed that: (1) Based on the analysis of the completeness of teaching practice assessment component used batik competence in schools needs to be a change in the form of an assessment tool that is used to facilitate the processing of value. The lack of clarity of criteria and assessment standards of competence batik practices that will be used in the assessment visits of competency assessment tools batik batik preparation phase. Lack of clarity and comprehensiveness of the assessment criteria of competence batik practices used in the assessment visits of competency assessment tools batik batik process stage. Lack of clarity of assessment criteria practice competencies batik used in the assessment visits of assessment tools competency batik stage products of batik (2) the development of the completeness of the equipment components competency assessment batik in the form of changes in the types of assessment tools and evaluation aspects are used, the development of an assessment tool preparation stage additional form aspects of the assessment that aspect of workwear and apparatus, batik, materials batik, tool development assessment phase of the work process in the form of additional aspects of the assessment in accordance with the batik process of designing a motive to end product, the development of an assessment tool stage product results in the form of additional aspects of the assessment consistenses form of ornaments / the graffiti canting, the overall results of the product as well as time. The final result of this study is an assessment tool that has been developed batik competency as a whole has been able to photograph the process of batik cloth made in school. Recommendations from this study hopefully batik competency assessment tool that has been developed to be an example of batik and competence assessment tool was applied in the assessment process of learning batik competence in school.